Cardiac magnetic resonance imaging in differential diagnosis of cardiac masses. (8th February 2021) - D"angelo, EC; Paolisso, P; Bergamaschi, L; Foa, A; Magnani, I; Rinaldi, A; Toniolo, S; Angeli, F; Bartoli, L; Donati, F; Renzulli, M; Rucci, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): S. Orsola Hospital Background:  Differential diagnosis of cardiac masses represents a challenging issue with important implications for therapeutic management and patient's prognosis. Cardiac Magnetic Resonance (CMR) is a non-invasive imaging technique used to characterize morphologic and functional features of masses. Integration of these information can lead an accurate diagnosis. Purpose:  To evaluate the diagnostic role of CMR in defining the nature of cardiac masses. Methods  : Ninety-three patients with cardiac masses evaluated with CMR were enrolled. All masses had histological certainty. CMR sequences allowed a qualitative morphologic description as well as tissue characterization. Evaluation of masses morphology included localization, size and borders assessment, detection of potential multiple lesions and pericardial effusion. Tissue characterization resulted from an estimation of contrast enhancement - early gadolinium enhancement (EGE) and late gadolinium enhancement (LGE) sequences - and tissue homogeneity in T1 and T2 weighted acquisitions. The descriptive analysis was carried out by comparing benign vs malignant lesions as well as dividing patients into 4 subgroups: primitive benign tumours, primitive malignant tumours, metastatic tumours and pseudotumours.  Results:  The descriptive analysis of the morphologic features showed that diameter > 50mm, invasion of surrounding planes, irregular margins and presence of pericardial effusion were able to predict malignancy (p < 0.001). As for tissue characteristics, heterogeneous signal intensity - independently from T1 and T2 weighted acquisitions - and EGE were more common in malignant lesions (p <0.001). When analysing the four subgroups, CMR features did not discriminate between primitive malignant masses and metastasis. Conversely, hyperintensity signal and EGE were able to distinguish benign primitive lesions from pseudotumors (p = 0.002).  Furthermore, using classification and regression tree (CART) analysis, we developed an algorithm to differentiate masses: invasion of surrounding planes was a common characteristic of malignancy and identifies itself malignant tumors. In the absence of invasive features, gadolinium enhancement was evaluated: the lack of contrast uptake was able to exclude a pseudotumor diagnosis and reduced the probability of a primary benign tumor.  Conclusions: Cardiac magnetic resonance is a very powerful diagnostic tool for differential diagnosis of cardiac masses as it correctly addresses malignancy. Furthermore, an accurate evaluation of the several CMR features, may discriminate primary benign masses and pseudotumours.